Therapeutic effects of acupuncture therapy for kidney function and common symptoms in patients with chronic kidney disease: a systematic review and meta-analysis - Shan Liu; Fan Zhang; Yan Bai; Liuyan Huang; Yifei Zhong; Yi Li (Renal Failure)
Purpose The number of clinical reports of acupuncture therapy in chronic kidney disease (CKD) is gradually increasing. This systematic review and meta-analysis aim to examine the therapeutic role of acupuncture therapy in kidney function and common symptoms in CKD patients.Methods We searched Embase, PubMed, Scopus, Web of Science, China National Knowledge Infrastructure, WanFang, and WeiPu for randomized controlled trials comparing acupuncture treatment with control or placebo groups. We assessed the effect of acupuncture therapy in CKD patients using a meta-analysis with the hartung-knapp-sidik-jonkman random effects model. In addition, we visualized keyword co-occurrence overlay visualization with the help of VOSviewer software to describe the research hotspots of acupuncture therapy and CKD.Results A total of 24 studies involving 1494 participants were included. Compared to the control group, acupuncture therapy reduced serum creatinine levels (standardized mean difference [SMD]: −0.57; 95% CI −1.05 to −0.09) and relieved pruritus (SMD: −2.20; 95% CI −3.84, −0.57) in patients with CKD, while the TSA showed that the included sample size did not exceed the required information size. The included studies did not report acupuncture-related adverse events.Conclusions Acupuncture is an effective and safe treatment for improving kidney function and relieving pruritic symptoms in patients with CKD, but the very low evidence may limit this conclusion. The TSA suggests that high-quality trials are needed to validate the efficacy of acupuncture therapy.